2020
DOI: 10.1021/acssuschemeng.0c03903
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Bio-pitch from Bio-oil

Abstract: Coal-tar-pitch (CTP) is a fossil carbon material, currently used as a the binder in carbon anode manufacturing process. Regardless of the technical benefits of coal-tar-pitch, it contains polycyclic aromatic hydrocarbons (PAHs), known to be carcinogenic for humans and detrimental to the environment. To overcome this challenge, research was carried out to search for a suitable substitution with health- and environmental-friendly properties. Bio-pitch, produced from bio-oil, could be a potential alternative bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…A detailed description of the properties of bio-oil, CTP, and calcined petroleum coke for this study can be found elsewhere. 4,6 Synthesis of Biopitch. The biopitch samples were synthesized from bio-oil using vacuum distillation process.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 3 more Smart Citations
“…A detailed description of the properties of bio-oil, CTP, and calcined petroleum coke for this study can be found elsewhere. 4,6 Synthesis of Biopitch. The biopitch samples were synthesized from bio-oil using vacuum distillation process.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The biopitch samples were synthesized from bio-oil using vacuum distillation process. 4 Different quantities of biochar powders (0, 0.5, 1.0, 1.5, 3.0, 6.0, and 9.0 wt %) were mixed with bio-oil prior to vacuum distillation. The mixture of bio-oil and biochar was heated from room temperature to the desired soaking temperature (180 °C) with a heating rate of 5 °C/min and then maintained for 3 h at this temperature under a reduced pressure (54 Torr) and slowly allowed to cool to room temperature.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The softening point and the density of the pitch are 1.310 g cm −3 and 109 C, respectively. Note that more information about the physical properties of the pitch is available at Lu et al [42,43] It is worth mentioning that 178 C is the forming temperature in anode production [1] ; however, this temperature could vary between 165-185 C depending on the smelter. The other two temperatures (T = 166 and 190 C) are chosen to study the effects of temperature on the rheological properties of the materials.…”
Section: Rheological Characterization 21 | Rheological Properties Of ...mentioning
confidence: 99%